Comparison of cost-effectiveness of implantable cardioverter defibrillator therapy in patients for primary prevention in Latin America: an analysis using the Improve SCA study. (1st January 2021) - Higuera, Lucas; Holbrook, Reece; Wherry, Kael; Rodriguez, Diego A.; Cuesta, Alejandro; Valencia, Juan; Arcos, Julián; López Gómez, Agustín
Abstract: Objective: The mortality benefit of implantable cardioverter defibrillators (ICDs) for primary prevention (PP) of sudden cardiac arrest (SCA) has been well-established, but ICD therapy remains globally underutilized. The results of the Improve SCA study showed a 49% relative risk reduction in all-cause mortality among ICD patients with 1.5 primary prevention (1.5PP) characteristics (patients with one or more risk factors, p  < 0.0001). We evaluated the cost-effectiveness of ICD compared to no ICD therapy among patients with 1.5PP characteristics in three Latin American countries and analyzed the factors involved in cost-effectiveness. Methods: We used a published Markov model that compares costs and outcomes of ICD to no ICD therapy from local payers' perspective and included country-specific and disease-specific inputs from the Improve SCA study and current literature. We used WHO-recommended willingness-to-pay (WTP) thresholds to assess cost-effectiveness and compared model outcomes between countries. Results: Incremental costs per QALY (quality-adjusted life year) saved by ICD compared to no ICD therapy are Colombian Pesos COP$46, 729, 026 in Colombia, Mexican Pesos MXN$246, 016 in Mexico, and Uruguayan Pesos UYU$1, 213, 614 in Uruguay in the base case scenario; all three figures are between 1–3-times GDP per capita for each country. One-way and probabilistic sensitivity analyses confirm the base case scenario results. Non-cardiac accumulated deaths are lower in Mexico, resulting in a comparatively increased cost-effective ICD therapy. Limitations: The Improve SCA study was not randomized, so clinical results could be biased; however, measures were taken to reduce this bias. Costs and benefits were modelled beyond the timeline of direct observation in the Improve SCA study. Conclusions: ICD therapy is cost-effective in Mexico and Uruguay and potentially cost-effective in Colombia for a 1.5PP population. Variability in ICER estimates by country can be explained by differences in non-cardiac deaths and cost inputs.